Al-Qur’an-Based Justice Scale: Construction and Psychometric Properties - Tahrir, Tahrir; Malik, Asep Saepudin; Augustiya, Tasya (Psikis : Jurnal Psikologi Islami, 2025)
The research was derived from the unavailability of a justice measuring instrument, according to the Qur'an, that has been made by previous researchers. Based on the phenomenon, the purpose of this research was to construct a justice measuring instrument in accordance with Qur'anic principles. The subjects in this research were 748 students of UIN Sunan Gunung Djati Bandung. Based on the results of the research, it is known that the definition of justice according to the Qur'an is to give something to each person per their rights; treat each individual absolute impartiality and equally, without discrimination, and uphold the balance between rights and obligations indiscriminately; and balance the achievements obtained with their needs and uses. Based on the results of the explanatory factor analysis and confirmatory factor analysis tests, it is known that justice as specified in the Qur'an consists of three dimensions with 11 indicators.